2019
DOI: 10.1155/2019/4814793
|View full text |Cite
|
Sign up to set email alerts
|

Improving Upconversion Photoluminescence of GdAlO3:Er3+, Yb3+ Phosphors via Ga3+, Lu3+ Doping

Abstract: GdAlO3:Er3+, Yb3+ phosphors doped with Lu3+, Ga3+ ions were prepared via coprecipitation. The influences of substituting Ga3+ for Al3+ and substituting Lu3+ for Gd3+ on the structure and upconversion photoluminescence (UCPL) of the phosphors were studied. The experimental results show that the crystal textures did not change but the lattice parameters changed slightly via Lu3+, Ga3+ doping. This results in a decrease in the host phonon energy and a marked improvement in the green emission spectrum at 546nm. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Generally, the process of coprecipitation method can be divided into five steps (Sun et al, 2020): (1) formation of mixtures (including precipitator, Ln 3+ salt, OA/OM, ODE) in a boiling temperature, (2) nucleation and growth, (3) precipitation, (4) filtration, and (5) calcination. Deng et al (2019) prepared GdAlO 3 :Er 3+ ,Yb 3+ phosphors doped with Lu 3+ and Ga 3+ ions via coprecipitation, which has introduced a new strategy for the synthesis of multiple codoped UCNPs. For the food contaminants analysis, Wang, Zhu, et al (2018) reported a novel UCNP of Eu/Sm/Mn co-doped CaS with 59.3% upconversion-luminescence quantum yield via using a simple coprecipitation method followed by a calcination technology.…”
Section: Coprecipitation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the process of coprecipitation method can be divided into five steps (Sun et al, 2020): (1) formation of mixtures (including precipitator, Ln 3+ salt, OA/OM, ODE) in a boiling temperature, (2) nucleation and growth, (3) precipitation, (4) filtration, and (5) calcination. Deng et al (2019) prepared GdAlO 3 :Er 3+ ,Yb 3+ phosphors doped with Lu 3+ and Ga 3+ ions via coprecipitation, which has introduced a new strategy for the synthesis of multiple codoped UCNPs. For the food contaminants analysis, Wang, Zhu, et al (2018) reported a novel UCNP of Eu/Sm/Mn co-doped CaS with 59.3% upconversion-luminescence quantum yield via using a simple coprecipitation method followed by a calcination technology.…”
Section: Coprecipitation Methodsmentioning
confidence: 99%
“…Deng et al. (2019) prepared GdAlO 3 :Er 3+ ,Yb 3+ phosphors doped with Lu 3+ and Ga 3+ ions via coprecipitation, which has introduced a new strategy for the synthesis of multiple co‐doped UCNPs. For the food contaminants analysis, Wang, Zhu, et al.…”
Section: Rational Design Strategy To Construct Upconversion‐based Sen...mentioning
confidence: 99%
“…Ga 3+ is Al 3+ and Lu 3+ is Gd 3+ substituted, and a change in the intensity of the up-conversion green emission according to the structural change in the host was reported. 17 Barrera et al synthesized an up-conversion phosphor by doping Er 3+ and Yb 3+ ions into a KY(WO 4 ) 2 host using the Pechini method. The phosphor excited at 980 nm showed emission spectra of 530, 550, and 660 nm.…”
Section: Introductionmentioning
confidence: 99%